Strategies for Strengthening Digital Media in the Delivery of Humanitarian Law Information in the Era of Society 5.0 - Victor Andhika Tjokro; Tidar Hary Nugroho (IRDH International Journal of Social Sciences & Humanities, 2025)
Digital media plays a crucial role in accelerating the distribution of information related to humanitarian law. The goal of this research is to develop a strategy to strengthen the role of digital media in delivering information about humanitarian law in the era of Society 5.0. This research employs a qualitative descriptive approach. Data in this qualitative descriptive study were collected from various documents and literature, including reference books and scientific articles. The data analysis method used in this study is the SOAR (Strengths, Opportunities, Aspirations, Results) approach. The research results indicate that there are 7 strengths and 4 opportunities that digital media possesses in conveying information about humanitarian law. From these strengths and opportunities, five aspirations were obtained which serve as the basis for formulating strategies to strengthen the role of digital media. Strategies for Strengthening Digital Media in the Delivery of Humanitarian Law Information in the Era of Society 5.0 can be reinforced and developed by carrying out the following roles (1) Organizing human resource training for TNI personnel developed to enhance the capabilities of TNI personnel in the professional management of digital media, (2) Organizing training for TNI personnel in the development of Artificial Intelligence, (3) Encouraging the authorities to formulate regulations that govern the development of intelligent and accurate digital media in the implementation of humanitarian law, (4) Creating effective and targeted digital content in the delivery of humanitarian law information, and also (5) Managing digital media professionally, so that humanitarian law information can be disseminated effectively to the public.